Formulation and Evaluation of Sustained-Release Tablets of Jatropha curcas L. Leaf Extract Using HPMC and Xanthan Gum Matrix for Antihypertensive Therapy - Maghfirah, Suci; Puteri, Cut Intan Annisa; Dalimunthe, Gabena Indrayani; Lubis, Minda Sari (Pustaka Media Publishing, 2025)
The development of pharmaceutical technology has enabled the formulation of sustained-release tablets to improve therapeutic efficacy and patient compliance in antihypertensive therapy. This study aimed to evaluate the potential of Jatropha curcas L. leaf extract as an active ingredient in sustained-release tablets using hydroxypropyl methylcellulose (HPMC) and xanthan gum as matrix-forming polymers. The extract was obtained by maceration with 96% ethanol, and tablets were prepared using the wet granulation method. Granule flow properties and tablet physical characteristics (organoleptic properties, weight uniformity, size uniformity, hardness, friability, and disintegration time) were assessed, followed by dissolution studies in simulated gastric fluid (pH 1.2), intestinal fluid (pH 4.5), and intestinal fluid (pH 7.4). Results showed that all formulations met pharmacopeial requirements. Formula III, containing HPMC and xanthan gum in a 2:1 ratio, demonstrated the longest disintegration time (113 minutes) and the slowest drug release profile (54.80% within 480 minutes). These findings suggest that this formulation has the potential to serve as an optimal sustained-release tablet of Jatropha curcas L. extract for antihypertensive therapy.